A comparative evaluation of differently synthesized high surface area carbons for Li-ion hybrid electrochemical supercapacitor application: Pore size distribution holds the key - Suryawanshi, Anil (2017)
We report a comparative evaluation of carbonaceous cathodes synthesized by different protocols in the context of Li-ion hybrid electrochemical supercapacitors (Li-HEC) application. The four cathode materials compared include hierarchically perforated graphene (HPGN), Polymer (Poly (4-styrene sulfonic acid-co-maleic acid) sodium salt) derived Graphene (PDG), dead Neem leaves derived carbon (LDC) and commercial activated carbon (CAC). All these carbons exhibit high specific surface area with excellent porosity. In the single electrode configuration (vs. Li), HPGN shows maximum specific capacitance of ∼155 F g−1 with good cycleability over 1000 cycles (99.5% retention). On the other hand, there is no obvious distinctive difference between the specific capacitance values for the rest of the carbonaceous materials tested. The Li-HEC is constructed with spinel phase Li4Ti5O12 anode and carbonaceous materials described above as cathode in a non-aqueous medium. Amongst the various cases the Li-HEC with HPGN delivered maximum energy and corresponding power density of 65 Wh kg–1 and 0.5 kW kg−1, respectively with excellent cycleability as compared to the rest of the materials, tested in the same configuration under the same testing conditions.